Numerical simulation on flow and heat transfer characteristics of a single-loop oscillating heat pipe with variable pipe diameter ratios - Lu, Hongkun; Noor, M. M.; Ning, Shuigen; K., Kadirgama (Semarak Ilmu Publishing, 2024)
A three-dimensional numerical model, employing the Volume of Fluid (VOF) method, was developed for a single-loop oscillating heat pipe (OHP) with variable diameters. The investigation explored the impact of varying pipe diameter ratios on flow and heat transfer characteristics at different operational stages under a 40W heat power. The results reveal that the diameter ratio significantly affects the spatial arrangement of the evaporation, adiabatic, and condensation sections in the OHP. In the initial stage, the condensation section displays 15 liquid slugs when the diameter ratio is 1, but this number decreases to fewer than 10 in the same area when the diameter ratio exceeds 1. Comparative to a straight-pipe OHP, configurations with varying diameter ratios exhibit a marginal reduction in the average fluid velocity during the circulation of the working fluid inside the pipe, with the most pronounced velocity decrease occurring at a diameter ratio of 0.8. As the diameter ratio increases to 1.25 and 1.5, the turbulent disturbances in the region where the working fluid flows from the adiabatic section to the evaporation or condensation section intensify, facilitating the temperature exchange within the OHP. During stable operation of the OHP, the frequency of temperature oscillations increases with an increasing diameter ratio, while the amplitude decreases. Among all the cases, the OHP with a diameter ratio of 1.25 has the optimal heat resistance, 1.50K/W. The heat transfer performance of the OHP with a pipe diameter ratio of 0.8 deteriorated, and the thermal resistance increased by 27.6% compared with the straight-pipe OHP.